Dose selection for aztreonam-avibactam, including adjustments for renal impairment, for Phase IIa and Phase III evaluation - Shampa Das; Todd Riccobene; Timothy J. Carrothers; James G. Wright; Merran MacPherson; Andrew Cristinacce; Lynn McFadyen; Rujia Xie; Alison Luckey; Susan Raber (European Journal of Clinical Pharmacology, 2024)
Purpose A series of iterative population pharmacokinetic (PK) modeling and probability of target attainment (PTA) analyses based on emerging data supported dose selection for aztreonam-avibactam, an investigational combination antibiotic for serious Gram-negative bacterial infections. Methods Two iterations of PK models built from avibactam data in infected patients and aztreonam data in healthy subjects with “patient-like” assumptions were used in joint PTA analyses (primary target: aztreonam 60% f T > 8 mg/L, avibactam 50% f T > 2.5 mg/L) exploring patient variability, infusion durations, and adjustments for moderate (estimated creatinine clearance [CrCL] > 30 to ≤ 50 mL/min) and severe renal impairment (> 15 to ≤ 30 mL/min). Achievement of > 90% joint PTA and the impact of differential renal clearance were considerations in dose selection. Results Iteration 1 simulations for Phase I/IIa dose selection/modification demonstrated that 3-h and continuous infusions provide comparable PTA; avibactam dose drives joint PTA within clinically relevant exposure targets; and loading doses support more rapid joint target attainment. An aztreonam/avibactam 500/137 mg 30-min loading dose and 1500/410 mg 3-h maintenance infusions q6h were selected for further evaluation. Iteration 2 simulations using expanded PK models supported an alteration to the regimen (500/167 mg loading; 1500/500 mg q6h maintenance 3-h infusions for CrCL > 50 mL/min) and selection of doses for renal impairment for Phase IIa/III clinical studies. Conclusion A loading dose plus 3-h maintenance infusions of aztreonam-avibactam in a 3:1 fixed ratio q6h optimizes joint PTA. These analyses supported dose selection for the aztreonam-avibactam Phase III clinical program. Clinical trial registration : NCT01689207; NCT02655419; NCT03329092; NCT03580044.